2001
DOI: 10.1080/00071660120070622
|View full text |Cite
|
Sign up to set email alerts
|

Insulin administration suppresses an increase in insulin-like growth factor binding protein-2 gene expression stimulated by fasting in the chicken

Abstract: 1. We examined the changes in plasma IGF-I concentration and tissue IGFBP-2 gene expression of young fasted chickens refed a commercial diet or administered bovine insulin intravenously. 2. Plasma IGF-I concentration was decreased by fasting for 2 d. Although plasma IGF-I concentration was increased by refeeding, it didn't recover to the level of chickens fed a commercial diet ad libitum. 3. Insulin administration lowered plasma IGF-I concentration compared to other groups. 4. Hepatic IGFBP-2 mRNA was increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…IGFBPs are thought to prolong the half-life of circulating IGFs (Cohen & Nissley 1976) and also act as modulators of IGF activity (Elgin et al 1987;Rutanen et al 1988). The depression of IGFBP-2 gene expression enhanced by refeeding was highly associated with the elevation in plasma insulin concentration stimulated by refeeding (Nagao et al 2001), and it was suggested that little change in plasma insulin level might be brought about by protein starvation and the supplementation with methionine and/or glycine to the protein-free diet. However, in the present study no influence of feeding a proteinfree diet and the supplementation of methionine and/or glycine to the protein-free diet on tissue IGFBP-2 gene expression was observed (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IGFBPs are thought to prolong the half-life of circulating IGFs (Cohen & Nissley 1976) and also act as modulators of IGF activity (Elgin et al 1987;Rutanen et al 1988). The depression of IGFBP-2 gene expression enhanced by refeeding was highly associated with the elevation in plasma insulin concentration stimulated by refeeding (Nagao et al 2001), and it was suggested that little change in plasma insulin level might be brought about by protein starvation and the supplementation with methionine and/or glycine to the protein-free diet. However, in the present study no influence of feeding a proteinfree diet and the supplementation of methionine and/or glycine to the protein-free diet on tissue IGFBP-2 gene expression was observed (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study no influence of feeding a protein‐free diet and the supplementation of methionine and/or glycine to the protein‐free diet on tissue IGFBP‐2 gene expression was observed (data not shown). The depression of IGFBP‐2 gene expression enhanced by refeeding was highly associated with the elevation in plasma insulin concentration stimulated by refeeding (Nagao et al . 2001), and it was suggested that little change in plasma insulin level might be brought about by protein starvation and the supplementation with methionine and/or glycine to the protein‐free diet.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, insulin could strongly suppress basal (Böni-Schnetzler et al 1990) and RA (retinoic acid)-induced (Schmid et al 1992) IGFBP-2 mRNA levels in rat hepatocytes. Insulin administration also decreased chicken hepatic and gizzard IGFBP-2 gene expression stimulated by fasting (Nagao et al 2001). We also found the putative binding sites of CREB (cAMP-response element binding protein) and GR (glucocorticoid receptor) in the promoter of goldfish IGFBP-2 (our unpublished data).…”
Section: Discussionmentioning
confidence: 62%
“…Therefore, it seems likely that the upregulation of hepatic IGFBP-1 and -2 expression may contribute to the suppression of IGF effects under the fasting condition in chickens. Nagao et al (2001) reported that intravascular administration of insulin reversed the fasting-induced increase in hepatic IGFBP-2 mRNA in layer chickens.…”
Section: Resultsmentioning
confidence: 99%